The role of ethics in improving the quality of public services - Pandu Pamungkas; Irsad Munawir (Privietlab, 2025)
Ethics play a fundamental role in shaping the quality of public services, providing the foundation for professionalism, transparency, accountability, and fairness in governance. This study aims to analyze the role of ethics in improving public service delivery through a comprehensive literature review. By employing a descriptive qualitative approach and library research method, this study synthesizes insights from books, peer-reviewed journal articles, laws and regulations, official institutional reports, and international publications. The findings revealed that ethical standards significantly contribute to building public trust, preventing maladministration, and fostering clean governance. However, challenges persist in implementing ethics within the public sector, including weak law enforcement, limited ethical awareness among officials, and the persistence of a patrimonial bureaucratic culture. To address these obstacles, this study highlights the need to strengthen bureaucratic reform, integrate ethics education into civil service training, and enhance participatory monitoring systems. This study contributes both theoretically and practically by emphasizing ethics as an indispensable pillar of good governance and offering recommendations to enhance the effectiveness, fairness, and accountability of public services.